16. A Randomized Phase 1 Study of a Novel Pneumococcal Conjugate Vaccine in Healthy Japanese Adults in the United States. (31st December 2020) - Fitz-Patrick, David; Young Jr., Mariano; Scott, Daniel; Scully, Ingrid L; Baugher, Gary; Peng, Yahong; Jansen, Kathrin U; Gruber, William C; Watson, Wendy
Abstract: Background: Because of the number and variability of serotypes causing pneumococcal disease among different geographic regions, age groups, and environmental backgrounds, expanding serotype coverage with pneumococcal conjugate vaccines (PCVs) is a continued unmet need. Methods: This phase 1, randomized, double-blind study included healthy Japanese adults aged 18–49 years residing in the United States. Subjects were randomized 1:1:1 to receive a single dose of a 20-valent PCV (containing 13-valent PCV [PCV13] serotypes plus 8, 10A, 11A, 12F, 15B, 22F, 33F), a novel pneumococcal polysaccharide conjugate vaccine with extended coverage, or PCV13 (control). Safety was the primary endpoint and included reactogenicity events occurring ≤ 14 days after vaccination, adverse events (AEs) ≤ 1 month after vaccination, and serious AEs (SAEs) ≤ 6 months after vaccination. The secondary endpoint was pneumococcal serotype-specific immunogenicity as determined by opsonophagocytic activity (OPA) titers on sera collected before and 1 month after vaccination. Results: Overall, 35 subjects received PCV20 and 35 subjects received PCV13. One subject withdrew before the 1-month follow-up. Local reactions and systemic events across groups were generally mild or moderate (Figure 1 ). Two vaccine-related AEs occurred (injection site erythema and swelling in the PCV20 group); no severe AEs, SAEs, or safety-related withdrawals were reported. OPA geometric mean titers increased for all 20 serotypes in the PCV20 group and all 13 serotypes in the PCV13 group 1 month after vaccination; corresponding OPA geometric mean fold rises from baseline to 1 month after vaccination are reported (Figure 2; Figure 3 ). Figure 1 Figure 2 Figure 3 Conclusion: PCV20 was well tolerated and induced serotype-specific functional OPA immune responses that are anticipated to be associated with protection in Japanese adults. ClinicalTrials.gov: NCT03642847. Funding: Pfizer Inc. Disclosures: David Fitz-Patrick, MD, Pfizer Inc (Grant/Research Support) Mariano Young Jr., MD, Pfizer Inc (Employee, Shareholder) Daniel Scott, MD, Pfizer (Employee, Shareholder) Ingrid L. Scully, PhD, Pfizer Inc (Employee, Shareholder) Gary Baugher, PharmD, Pfizer Inc (Employee, Shareholder) Yahong Peng, PhD, Pfizer (Employee, Shareholder) Kathrin U. Jansen, PhD, Pfizer (Employee, Shareholder) William C. Gruber, MD, Pfizer (Employee, Shareholder) Wendy Watson, MD, Pfizer (Employee, Shareholder)